The Effect of Android-Based Contextual Teaching Materials on Students' Physics Problem-Solving Skills - Rahmatullah Rahmatullah; Fuad Tamami; Surya Jatmika; Ibrahim Ibrahim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The integration of technology into learning needs to be done following the times. Many learning resources are still not integrated with technology that it hinders the attainment of students' problem-solving skills. Therefore, this research aims to determine the effect of android-based contextual teaching materials on students' problem-solving skills. This research is quasi-experimental with a pretest-posttest control group design. The research population was all students of class X of SMAN 3 Mataram. The research sample used class X MIA 3 as the control group and class X MIA 5 as the experimental group. The data collection instrument used a test with several problem-solving indicators. Problem indicators used include solving, planning, explaining solutions, and evaluating. Data analysis used t-test and N-gain to see the magnitude of the effect. The results of the t-test showed a data significance value of 0.004. This result is still below the α value (sig. < 0.05), meaning that there is a positive effect from the treatment given. The experimental group got a higher increase than the control group. The difference in the increase occurred for the sub-materials and all indicators of problem-solving skills. Therefore, the conclusion of the study is that android-based contextual teaching materials have a positive effect on students' physics problem-solving skills.